Associação de piretroides nanoencapsulados ou não com sinergistas para o manejo da resistência de Chrysodeixis includens (WALKER) e Euschistus heros (F.) - Boff, Jéssica Santi (2022)
The brown stink bug, Euschistus heros (F.) (Hemiptera: Pentatomidae), and the soybean looper, Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae), are the main pests of soybean in South America. Chemical control is the main strategy for controlling these insectspest, however, low susceptibility to pyrethroids was reported in Brazil for both species. In the first study, it was evaluate the addition of synergists piperonyl butoxide (PBO) and diethyl maleate (DEM) to manage E. heros and C. includens with resistance to λ-cyhalothrin and bifenthrin. The LD50 of technical grade and commercial products containing λ-cyhalothrin and bifenthrin decreased against field-collected E. heros exposed to PBO and DEM relative to unexposed insects; synergistic ratios up to 4.75-fold. The mortality also increased when E. heros were exposed at fixed doses of commercial λ-cyhalothrin (from 4% to 44%) and bifenthrin (from 44% to 88%) in the presence of synergists. There was also a higher susceptibility of field-collected C. includens to technical grade λ-cyhalothrin when PBO was used; synergistic ratio of 5.50-fold. A high lethally of technical grade λ-cyhalothrin was also verified in the presence of PBO, with mortality increasing from 6% to 57%. In the second study, we developed and evaluated nanoencapsulated-based bifenthrin and λ-cyhalothrin with the synergistic compounds PBO and DEM for resistance management of E. heros and C. includens. Nanoformulations of bifenthrin and λ-cyhalothrin with PBO and DEM presented good physical-chemical characteristics and stability in function of the time (>90 days). It was also observed that the spherical morphology of all prepared systems and the encapsulation efficiency in nanostructured lipid carrier systems did not change with the addition of synergists. In toxicological bioassays, nanoencapsulated bifenthrin with DEM increased the susceptibility of E. heros to bifenthrin by 3.50-fold, as indicated by LC90 values. A high susceptibility to nanoencapsulated bifenthrin and λ-cyhalothrin with PBO was also detected in C. includens, reveling a synergistic ratio up to 2.16-fold according to LC90 values. We also found that nanoencapsulated bifenthrin and λ-cyhalothrin with PBO and DEM increased mortality of E. heros (68% and 72%) and C. includens (33% and 21%), compared to commercial products with bifenthrin and λ-cyhalothrin. Our results indicate the utility of synergists in reversing λ-cyhalothrin and bifenthrin resistance in E. heros and C. includens and suggest a significant role of metabolic mechanisms in the detoxification of both pyrethroids. We also reported that it is possible to develop nanoencapsulated-based formulations of bifenthrin and λ-cyhalothrin with the synergists PBO and DEM, which demonstrate the potential to restore the susceptibility of E. heros e C. includens to pyrethroids. This is the first study to report the development of nanoencapsulated insecticides with synergists for insect resistance management.